Impedance spectra measurements of solids - Zima, Vítězslav (Univerzita Pardubice, 1996)
A system for impedance spectra measurement is described. Two examples (polycrystalline sample of VOPO4 intercalated with sodium cation and As2Se3 glass doped with silver) are given to demonstrate the possibilities of this method.